2013
DOI: 10.1105/tpc.113.115691
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Glucosidases and Protein Quality Control Factors Cooperate to Establish Biotrophy inUstilago maydis 

Abstract: Secreted fungal effectors mediate plant-fungus pathogenic interactions. These proteins are typically N-glycosylated, a common posttranslational modification affecting their location and function. N-glycosylation consists of the addition, and subsequent maturation, of an oligosaccharide core in the endoplasmic reticulum (ER) and Golgi apparatus. In this article, we show that two enzymes catalyzing specific stages of this pathway in maize smut (Ustilago maydis), glucosidase I (Gls1) and glucosidase II b-subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 60 publications
0
42
1
Order By: Relevance
“…In eukaryotes, N ‐linked glycoproteins undergo a quality control cycle, known as the calnexin cycle, which ensures that only correctly folded glycoproteins are secreted (Ruddock & Molinari, ). Calnexin (Cne1), a membrane‐bound chaperone and central component of this cycle, is dispensable for virulence in U. maydis (Fernández‐Álvarez et al ., ). To test whether Dnj1 has a partially redundant function with Cne1, we generated single ∆ cne1 and double ∆ dnj1 ∆ cne1 mutants in SG200.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In eukaryotes, N ‐linked glycoproteins undergo a quality control cycle, known as the calnexin cycle, which ensures that only correctly folded glycoproteins are secreted (Ruddock & Molinari, ). Calnexin (Cne1), a membrane‐bound chaperone and central component of this cycle, is dispensable for virulence in U. maydis (Fernández‐Álvarez et al ., ). To test whether Dnj1 has a partially redundant function with Cne1, we generated single ∆ cne1 and double ∆ dnj1 ∆ cne1 mutants in SG200.…”
Section: Resultsmentioning
confidence: 97%
“…In plant infection assay, SG200∆cne1 was only slightly reduced in virulence (Fig. S3d), confirming previous observations (Fernández‐Álvarez et al ., ). Conversely, presumably because of the severe growth defect, SG200∆dnj1∆cne1 failed to cause any disease symptoms (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the role of N-glycosylation in the pathogenesis of filamentous fungi remains largely unexplored. To date, there are only three reports with glycosylation-related mutants in Ustilago maydis and Mycosphaerella graminicola that implicate N-glycosylation in the pathogenesis of plant pathogenic fungi (Schirawski et al, 2005;Motteram et al, 2011;Fernández-Álvarez et al, 2013). However, the underlying mechanism was not characterized in those studies; therefore, it is not clear why N-glycosylation is important for fungal pathogenesis.…”
Section: Introductionmentioning
confidence: 90%
“…Three earlier reports have shown that N-glycosylation plays an important role in the pathogenesis of plant pathogenic fungi. In U. maydis, the ER glucosidase I gene, Gls1, is required for the initial stages of infection following appressorium penetration (Fernández-Álvarez et al, 2013) and deletion of the ER glucosidase II gene, GAS1, resulted in arrested growth of IH in the epidermal cell layer of maize (Zea mays) (Schirawski et al, 2005), and in M. graminicola, the a-1,2-mannosyltransferase Alg2 was shown to be important for switching from the yeast-like phase to the hyphal form (Motteram et al, 2011). These studies suggested the importance of N-glycosylation of proteins in the pathogenesis of plant fungal pathogens but did not offer mechanistic insight into why N-glycosylation is important for pathogenesis in plant pathogens.…”
Section: Discussionmentioning
confidence: 99%